Health and safety - UNISON poster, c. 1990 (London, 1990)
1990 1980-95 "Health and safety - UNISON poster, c. 1990" [BW0064], 1990, Trades Union Congress This poster produced jointly by UNISON and the National Back Pain Association highlights injuries caused by lifting.